A magyar tudományos gyűjtemények trianoni veszteségei - Sipos, Anna Magdolna (Közép-Európai Közlemények, 2010)
Increasingly it is apparent that Trianon Treaty and its historic impact is still being debated in Hungary and that it is capable of generating a variety of discourses in the public domain. The theme deserves a more scientifically oriented in-depth exploration from the perspectives of the social sciences. The most important macrosocial effects, such as territorial, demographic, economic, and financial losses with regard to the historic decision have been appropriately analyzed in scholarly works written mainly in the first half of the 20th century and their findings have become embedded within public knowledge. This is not the case with the cultural and scientific aspects. Research institutes, libraries, museums, archives, and other relevant communities of the artistic, literary and civic fields, were cut off by the then newly formed borders causing not only a material loss but unreparable damage to intellectual life of Hungarians. The paper provides data and a comprehensive coverage of the library collections and repositories in order to contribute to the scientific investigation into the question of intellectual losses.